A study of single and two-plane balancing using influence coefficient method / Wan Sulaiman Wan Mohamad, Ahmad Azlan Mat Isa and M.A Ismail - Wan Mohamad, Wan Sulaiman; Mat Isa, Ahmad Azlan; M.A Ismail (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
Unbalance effect on rotating element is a condition resulted from an off centered mass concentration about a rotor s rotating centerline which will then generate centrifugal forces with increasing running speeds. This phenomenon will bring about excessive noise and vibration which in turn causing damages to the rotating elements and its support mechanism. To overcome this problem, a correction is required so as to minimize the excessive vibration as low as possible. In this study, unbalance problems including single and two-plane balancing are studied extensively by using theoretical influence coefficient method followed by the experimental verifications. Experimental procedure is performed by using trial mass to calculate the influence coefficient and the corrected mass values as well as the phase angles. The studies cover the static and dynamics balancing for the single plane and two-plane balancing respectively. Finally, the vibration reduction of the rotor is compared theoretically and experimentally. Based on the results, the improved vibration reduction could be obtained reasonably for both single and two-plane balancing by using influence coefficient method.